Analysis of Customer Protection against Personal Data Abuse by Banks in Indonesia: A Case Study of Shari'ah Banks in Indonesia - Faqih Khudori, M. Bintang (Ilmu Hukum, Sharia and Law Faculty, Sunan Gunung Djati Islamic State University of Bandung, 2025)
Abstract: Protection of customer personal data in the Indonesian banking sector is increasingly becoming a major concern with the rapid development of digital technology. The shift of banking transactions to digital platforms increases the risk of data leaks and the threat of cyber-attacks, requiring stricter regulations to safeguard sensitive customer information. This article evaluates the effectiveness of personal data protection regulations, including the implementation of the recently enacted Personal Data Protection Law, which in Indonesian, is named Undang-Undang Perlindungan Data Pribadi (UU PDP), as well as banks' responsibilities in maintaining the confidentiality and security of customer data. Using a normative juridical approach, this research assesses the policies and implementation of data protection by banks in Indonesia. The results of the analysis show that although many banks have taken proactive steps to protect customer data, there are still significant challenges in implementing regulations and increasing public awareness. Therefore, additional measures are needed to strengthen personal data protection and increase customer confidence in the banking system.